Towards the development of direct methodology to enantioenriched α-alkylated aldehydes - Charlton, A (2013)
Enantiopure α-alkyl-substituted aldehydes are widely recognised as important building blocks in synthesis. Despite this, methods to prepare such substrates are limited. Strategically, asymmetric intermolecular SN2 α-alkylation represents a highly straightforward transformation, but still remains an elusive feat. This thesis describes efforts to address this challenge, with attempted access to enantioenriched α-alkyl aldehydes by way of C-alkylation of chiral, non-racemic, hindered aldenamines using simple alkyl halides. Enamines derived from four types of auxiliary (a tropane, an oxazolidine, a pyrrolidine and a homotropane) have been prepared, and their alkylation profile examined. While the desired levels of asymmetric induction were not attained, use of the tropane and homotropane auxiliaries, which differ only by a single methylene group, interestingly, gave complimentary diastereocontrol during alkylation with EtI. The observed stereoselectivity is supported by density functional studies performed for ethylation of both enamines. Additionally, in the course of preparing the homotropane a highly efficient asymmetric synthesis of a homotropinone bearing gem-α-substitution has been developed.